Conservação da qualidade pós-colheita de laranjas tratadas com 1-metilciclopropeno - Rosa, Cassia Inês Lourenzi Franco (2011)
Oranges are the leading citrus species cultivated in Brazil, with domestic production directed to exports of juice and fruit consumption, both for domestic and foreign markets. The rate of post-harvest losses in fruits is high implicating in the quantity and quality of the product. The knowledge of the factors that cause post-harvest deterioration is crucial for the development of techniques that reduce these losses. The use of 1-methylcyclopropene (1-MCP) on vegetables, has achieved positive results for several fruits and vegetables, however there are few researches about its effects on non-climacteric fruits such as oranges. This study aimed to evaluate the conservation and post-harvest quality in oranges cv. Folha Murcha, cv. Pera and cv. Valencia, by using 1-MCP and cooling over the period of 60- day storage, in three harvests. Respiration rate, ethylene concentration, skin color, TSS, TTA, vitamin C, phenolic compounds, total carotenoids, total and reducing sugars among others were analyzed at 0, 15, 30, 45 and 60 days storage. According to the results obtained, it was concluded that: the 1-MCP was not the one that provided greater post-harvest preservation of fruit and also delayed the change in skin color from green to yellow/orange Higher doses of 1-MCP caused chemical stress in the oranges analyzed, being responsible for the increase in rates of ethylene produced and increase in decay.